Exterior Orientation in a Box: Cost-Effective RTK/IMU-Based Photo Geotagging - M. Wieser; G. Verhoeven; B. Wild; N. Pfeifer (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This paper presents a small, cableless and cost-effective (circa € 500 in 2022) device that embeds an RTK-enabled GNSS receiver and IMU in a 3D printed case to record the exterior orientation of photos via the camera's hot shoe. This hardware solution was developed within the academic graffiti project INDIGO to enable a faster and more robust exterior orientation (via incremental SfM) of the hundreds of weekly acquired graffiti photographs. The device relies solely on commercially available open-source development components that require only minimal knowledge of electronics. Moreover, it is small enough not to disturb the photographer but still provide constant visual feedback about the device's overall and positional solution status. To realistically test the achievable positional and rotational accuracy, we acquired a dense network of graffiti photos in INDIGO's test area. This test showed that the device provides centimetre-accurate photo positions and one-degree accurate pitch and roll values. The heading or yaw is probably only usable to some extent since it primarily relies on magnetometer measurements, which get quickly disturbed in an urban environment. In addition, the test revealed that the camera's internal IMU can provide roll and pitch values with sub-degree accuracy.